Learning to Teach Mathematics for Social Justice: A Dialogic Reflection - Sethi, Jyoti (Voices of Teachers and Teacher Educators, 2018)
This study explores the entailments of learning to teach mathematics for social justice by actively engaging six elementary school teachers in a critical research process. Where in the researcher who is an elementary teacher herself collaborates with the other teachers to explore critical mathematics education through a task based programme. The goal is to blur the distinction between research, learning, and action by providing the researcher and the participants opportunities to collectively engage in a reflective dialogue towards social justice and in the process enabling each one to actualise their ways of knowing and growing to sustain their growth throughout their careers.